Tinjauan Yuridis terhadap Tindak Pidana Persetubuhan dengan Kekerasan pada Anak - Tongat, Tongat; Nugrono, Bastianto; Wibowo, Supolo Satyo (Fakultas Syariah INSURI Ponorogo, 2022)
The Republic of Indonesia, which is based on Pancasila and the 1945 Constitution, always regulates the behavior of its citizens through a series of regulations that are sourced from law. Cases of child sexual intercourse in this country tend to increase. This is one indicator of the poor quality of child protection. Article 20 of Law Number 35 of 2014 amendments to Law Number 23 of 2002 concerning Child Protection states that: